Field Current Control Strategy for Wound-Rotor Synchronous Motors Considering Coupled Stator Flux Linkage - Daeyeon Hwang; Bon-Gwan Gu (IEEE Access, 2020)
The direct axis (d-axis) stator winding and field winding of a wound-rotor synchronous motor (WRSM) are mutually coupled much like the primary and secondary windings in a transformer are. As the field winding has a large number of turns, small variations of the stator d-axis current can induce a great electromotive force (EMF) in the field windings. This induced EMF voltage disturbs field current regulation, invokes an unwanted field current response, and distorts the stator d-axis flux. In this work, a novel field current control strategy for the WRSM is proposed for compensating the disturbance by d-axis current in field winding. The coupling effect between the stator d-axis winding and field winding is analyzed by using a polynomial regression of the stator d-axis flux linkage. Based on an analysis of the coupling effect, the proposed strategy combines two control methods. First, feedforward control is applied to decouple the field current response from the coupled change in the stator d-axis current flux. Second, a method is used to adjust the d-axis current to ensure that the field inverter voltage is not saturated. Simulations and experiments are presented to verify the proposed control method, proving that the proposed field current control strategy successfully compensates for the field current ripples caused by variations in the coupled stator d-axis current flux.